Microstructural investigation of as-fabricated and heat-treated Inconel 625 and Inconel 718 fabricated by direct metal laser sintering: contribution of Politecnico di Torino and Istituto Italiano di Tecnologia (IIT) di Torino. Issue 4 (July 2016) - Marchese, Giulio; Bassini, Emilio; Calandri, Michele; Ambrosio, Elisa Paola; Calignano, Flaviana; Lorusso, Massimo; Manfredi, Diego; Pavese, Matteo; Biamino, Sara; Fino, Paolo
Abstract : The Ni-based superalloys are widely used in aerospace and aeronautic industries, but building complex shape components with conventional technologies is expensive. Nowadays, it is possible to use techniques such as direct metal laser sintering (DMLS) process to overcome this problem. In the present report are summarized the activities performed at the Department of Applied Science and Technology (DISAT) of Politecnico di Torino and Istituto Italiano di Tecnologia (IIT) di Torino on the development of Ni-based superalloys produced by DMLS. More precisely, we have studied the microstructure architectures of Inconel 625 and Inconel 718 produced by M270 Dual Mode version and the impact of different heat treatments on their microstructures in order to meet the industrial requirements.